SORPTION-CHROMATICITY DETERMINATION OF ACTIVE INGREDIENTS IN DRUG SUBSTANCE TETRACYCLINE HYDROCHLORIDE AND IN CYANOCOBALAMIN SOLUTION FOR INJECTION - A. A. Chaplenko; O. V. Monogarova; K. V. Oskolok; S. A. Chaplenko (Разработка и регистрация лекарственных средств, 2019)
The simple and available technique of determination of tetracycline in the form of colored complex with iron(III) ions and B12 vitamin in the form of the colored thiocyanate complex of cobalt(II) after a chemical mineralization of cyanocobalamin is offered. The analytes were separated from the accompanying components by sorption to polyurethane foam based on ethers. The conditions of sorption separation and measurement of analytical signal of these substances are optimized. The obtained results are in satisfactory agreement with data declared by the manufacturer. The adequacy of proposed approach is confirmed by results of indirect X-ray fluorescence analysis of tetracycline drug substance and injection solution B12 vitamin (cyanocobalamin).